Etude De La Qualité Agronomique Et Biochimique De Quelques Variétés De Niébé (Vigna Unguiculata (L) Walp (Fabaceae) Provenant De La Côte d’Ivoire - Auguste Denise, Boyé Mambe; Edwige Salomé, Yapo Sopie; Boni Clovis, Koffi N’dodo; Jacob, Kouassi N’dri; Charlotte, Tonessia Dolou; Faustin, Soko Dago; Kouadio, Ballo Esperence; Gogbeu, Seu Jonathan; Koutoua, Ayolié; Justin, Kouadio Yatty (European Scientific Journal, ESJ, 2016)
Cowpea is a legume consumed in Côte d'Ivoire. There are many cultivars whose seeds are widely available. This study aimed to determine some agronomic and physicochemical characteristics of some cowpea cultivars in order to identify differences and if possible select the best for appropriate uses. The study included 16 cultivars; the agro-morphological variability was assessed on the basis of eight parameters. The results showed that the accessions N21DR, N18ZR, N10BBrp produced more seeds in a relatively short growing cycle. For the biochemical characterization, parameters such as moisture, ash, protein, fat, total carbohydrates and energy value were determined by conventional methods. Differences were observed between the physicochemical parameters of the analyzed cultivars seeds. The cultivar (N19ZBoBp) recorded the highest protein content.